On some trematoda species of three genera Dictyonograptus Travassos, 1919; Platynosomoides yamaguti, 1971 and Skrjabinus (Bhalerao, 1936) (Dicrocoeliidae) - Le, Nguyen Thi; Doanh, Pham Ngoc (Academia Journal of Biology, 2015)
Dicrocoeliidae is a big trematoda family, including approximately 400 species belonging to 37 genera, but the taxonomy of this family is on discussion. Based on the characteristic of vitellaria, the genus Platynosomoides Yamaguti, 1971 is considered as a synonym of the genus Dictyonograptus Travassos, 1919. and the species Skrjabinus andersoni (Ko, 1976) should be placed into the genus Dictyonograptus. The readjusment and discriptions of 4 species of the genus Dictyonograptus Travassos, 1919 founded in Vietnam, which are Dictyonograptus babeensis Nguyen, 1977; D. krongpakensis comb. nov.; D. vietnamensis Nguyen, 1968 and D. muris (Stscherbakova, 1942) comb. nov., are also given in this paper.